Safety and immunogenicity of heterologous prime-boost immunization with viral-vectored malaria vaccines adjuvanted with Matrix-M™. Issue 45 (27th October 2017) - Venkatraman, Navin; Anagnostou, Nicholas; Bliss, Carly; Bowyer, Georgina; Wright, Danny; Lövgren-Bengtsson, Karin; Roberts, Rachel; Poulton, Ian; Lawrie, Alison; Ewer, Katie; V. S. Hill, Adrian
Highlights: Viral vectored malaria vaccines adjuvanted with Matrix-M were well tolerated. Addition of Matrix-M did not result in a reduction in cellular or humoral immunogenicity. These vaccines adjuvanted with Matrix-M can be used safely in combination regimes with vaccines requiring an adjuvant. Abstract: The use of viral vectors in heterologous prime-boost regimens to induce potent T cell responses in addition to humoral immunity is a promising vaccination strategy in the fight against malaria. We conducted an open-label, first-in-human, controlled Phase I study evaluating the safety and immunogenicity of Matrix-M adjuvanted vaccination with a chimpanzee adenovirus serotype 63 (ChAd63) prime followed by a modified vaccinia Ankara (MVA) boost eight weeks later, both encoding the malaria ME-TRAP antigenic sequence (a multiple epitope string fused to thrombospondin-related adhesion protein). Twenty-two healthy adults were vaccinated intramuscularly with either ChAd63-MVA ME-TRAP alone (n = 6) or adjuvanted with 25 μg (n = 8) or 50 μg (n = 8) Matrix-M. Vaccinations appeared to be safe and generally well tolerated, with the majority of local and systemic adverse events being mild in nature. The addition of Matrix-M to the vaccine did not increase local reactogenicity; however, systemic adverse events were reported more frequently by volunteers who received adjuvanted vaccine in comparison to the control group. T cell ELISpot responses peaked at 7-days post boost vaccination with MVA ME-TRAP in all three groups. TRAP-specific IgG responses were highest at 28-days post boost with MVA ME-TRAP in all three groups. There were no differences in cellular and humoral immunogenicity at any of the time points between the control group and the adjuvanted groups. We demonstrate that Matrix-M can be safely used in combination with ChAd63-MVA ME-TRAP heterologous prime-boost immunization without any reduction in cellular or humoral immunogenicity. Clinical Trials Registration NCT01669512.